Education of trainees, training and fellowships for head and neck oncologic and surgical training in the UK: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Simo, R; Robson, A; Woodwards, B; Niblock, P; Matteucci, P
Abstract: Since the previous edition of these guidelines, significant changes have taken place in the training and assessment of surgeons and oncologists who treat patients with head and neck cancer. For those intending to become head and neck surgeons, a fellowship in head and neck surgery is virtually mandatory. This paper summarises the current career structure to specialise in head and neck oncology and surgery in the UK. Recommendation: Trainees applying for head and neck surgical oncology consultant posts should have completed additional training in the subspecialty.